Synthesis, structure and properties of new heterometallic octanuclear Li2Na2Cu4 and decanuclear Li2Zn8 complexes. (1st November 2019) - Haldar, Shobhraj; Dutta, Nityananda; Vijaykumar, Gonela; Das, Arpan; Carrella, Luca; Oliver, Allen; Bera, Manindranath
Graphical abstract: Two novel heterometallic, an octanuclear Li2 Na2 Cu4 and a decanuclear Li2 Zn8, complexes have been prepared by exploiting the flexibility, chelating ability and bridging potential of a carboxylate-based multidentate ligand showing interesting coordination chemistry. While complex 1 shows the rare tridentate μ 3 : η 2 : η 1 : η 1 bridging mode of carboxylate and tetradentate μ 4 : η 2 : η 1 : η 1 : η 1 bridging mode of succinate, complex 2 displays fascinating anti-anti μ 2 : η 1 : η 1 bidentate bridging mode of carboxylate and tetradentate μ 4 : η 1 : η 1 : η 1 : η 1 bridging mode of succinate. Magnetic and thermal properties of 1 and 2 have been investigated in detail. Abstract: A carboxylate containing polydentate ligand in combination with exogeneous succinate (suc) has been used to stabilize heterometallic octanuclear [Li2 Na2 Cu4 (cpdp)2 (suc)2 (CH3 OH)2 (H2 O)4 ]Cl2 ·6H2 O (1 ) and decanuclear Na(H3 O)2 [Li2 Zn8 (cpdp)4 (suc)2 (H2 O)4 ]Cl2 Br3 ·6MeOH·19H2 O (2 ) complexes. The reaction of ligand H3 cpdp (H3 cpdp =  N, N' -bis[2-carboxybenzomethyl]- N, N' -bis[2-pyridylmethyl]-1, 3-diaminopropan-2-ol) with stoichiometric amounts of CuCl2 /sodium succinate, and ZnCl2 /sodium succinate, allowed isolation of complexes 1 and 2, respectively. Analyses of single crystal X-ray structures indicate that complex 1 is capped by two [Cu2 (cpdp)] + molecular building units and two succinate linkers, while complex 2 is overlaid by four [Zn2 (cpdp)] + molecular building units and two succinate linkers. Whereas complex 1 shows monodentate terminal and tridentate μ 3 : η 2 : η 1 : η 1 bridging coordination of carboxylate, and μ 4 :η 2 : η 1 : η 1 : η 1 bridging mode of succinate, complex 2 displays monodentate terminal and anti-anti μ 2 : η 1 : η 1 bidentate bridging coordination of carboxylate, and μ 4 : η 1 : η 1 : η 1 : η 1 bridging mode of succinate. To our knowledge, 1 is the first example of copper/lithium/sodium-based hetero-octanuclear complex with any class of bridging or non-bridging ligand showing three different binding modes of carboxylates. Again, 2 is also the first example of a hetero-decanuclear metallomacrocyclic complex with any class of bridging or non-bridging ligand combining both lithium and zinc. Variable temperature magnetic investigation of 1 discloses sensible antiferromagnetic interactions intermediated among the copper centers. Thermal behavior of 1 and 2 has been examined by thermogravimetric analysis indicating that the complexes are stable up to ∼430 °C.